Causes of accidents at construction sites - Abdul Hamid, Abdul Rahim; Abd. Majid, Muhd Zaimi; Singh, Bachan (Faculty of Civil Engineering, 2008)
The statistic of accidents at construction sites give us a picture that Malaysian construction industry is one of the critical sectors that need a huge and fast overhaul from the current site safety practices. Accident don’t just happen, they are caused by unsafe acts, unsafe conditions or both. Most accidents result from a combination of contributing causes and one or more unsafe acts and unsafe condition. In order to improve the overall safety performance we need to investigate the root causes of construction accidents. That knowledge could be utilised in formulating more conducive working conditions and environments at construction sites. Therefore, a study has been conducted to identify the causes of accident at construction sites. This study was started out by reviewing literature from journals, books and web pages. Then reported accidents cases kept by the Department of Occupational Safety and Health Malaysia (DOSH) were examined to investigate causes of accidents. Surveys using questionnaire forms were carried out to obtain data from respondents who are mainly contractors and the rest are developers and consultants firms all around countries that are well versed with the construction safety. The finding of this study reveals that accidents are the result of many contributing factors, causes, and sub causes. Some of the critical factors are unsafe method, human element, unsafe equipment, job site conditions, management, and unique nature of the industry. The causes of accidents in Malaysia were found to be similar to that mentioned in literature review. However, some of the causes are low in frequency of occurrence. The main cause of construction accidents found are the workers’ negligence, failure of workers to obey work procedures, work at high elevation, operating equipment without safety devices, poor site management, harsh work operation, low knowledge and skill level of workers, failure to use personal protective equipments and poor workers attitude about safety